2022
DOI: 10.1021/acsami.2c01334
|View full text |Cite
|
Sign up to set email alerts
|

Precise Control of a Yolk-Double Shell Metal–Organic Framework-Based Nanostructure Provides Enhanced Fire Safety for Epoxy Nanocomposites

Abstract: Nanomaterials derived from metal–organic frameworks (MOFs) are highly promising as future flame retardants for polymeric materials. The precise control of the interface for polymer nanocomposites is taking scientific research by storm, whereas such investigations for MOF-based nanofillers are rare. Herein, a novel yolk-double shell nanostructure (ZIF-67@layered double hydroxides@polyphophazenes, ZIF@LDH@PZS) was subtly designed and introduced into epoxy resin (EP) as a flame retardant to fill the vacancy of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Therefore, the integrated intensity ratio of I D / I G is indexed to the graphitization degree. For the char residue, the lower the I D / I G value, the stronger the barrier effect it possesses . The value for the Co-POSS-incorporated composite was 2.02, which was much lower than that for neat EP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the integrated intensity ratio of I D / I G is indexed to the graphitization degree. For the char residue, the lower the I D / I G value, the stronger the barrier effect it possesses . The value for the Co-POSS-incorporated composite was 2.02, which was much lower than that for neat EP.…”
Section: Resultsmentioning
confidence: 99%
“…For the char residue, the lower the I D / I G value, the stronger the barrier effect it possesses. 35 The value for the Co-POSS-incorporated composite was 2.02, which was much lower than that for neat EP. However, the value showed a further decrease for the MPOFs-incorporated composite, which was 1.87.…”
Section: Gaseous-phase and Condensed-phase Analysis For The Flame-ret...mentioning
confidence: 99%
“…At about 400 °C, the peak intensity of the pyrolysis products reaches the maximum, and the corresponding peaks appear at 829, 1171, 1510, 1744, and 2974 cm −1 for −C�CH 2 , C−O−C, C�C, C�O, and C−H, respectively. 44 After that, the kind of cracking products changes slightly, which is inseparable from the exhaustion of RPHNs, accompanied by further evolution of the condensed phase residual char formed at high temperatures. Meanwhile, at the two decomposition temperatures (353.6 and 507.8 °C) corresponding to rapid weight reduction, the peak locations of the pyrolysis products are almost identical, suggesting that the gaseous products are extremely similar (Figure 7c), which can be attributed to only one functional flame-retardant additive in the matrix.…”
Section: Condensed and Gaseousmentioning
confidence: 99%
“…Metal ions can promote the cross‐linking of degraded fragments during the thermal degradation of polymers, so smoke suppression in polymer systems has been extensively studied. Meanwhile, the transition metal ions can promote the catalytic carbonization of the substrate during the combustion process and provide important assistance to the flame retardation of the condensed phase 8,9 . It is reported that iron compounds may act as a synergist and smoke suppressant in some thermoplastic polymers 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the transition metal ions can promote the catalytic carbonization of the substrate during the combustion process and provide important assistance to the flame retardation of the condensed phase. 8,9 It is reported that iron compounds may act as a synergist and smoke suppressant in some thermoplastic polymers. 10 The incorporation of a small number of iron compounds will cause the highly activated carbon to pass through the cross-linking reaction in the polymer.…”
mentioning
confidence: 99%